PENGGUNAAN DIKSI DALAM PENULISAN QUOTES PADA MEDIA SOSIAL TIK TOK (The Use Of Diction In Writing Quotes On Tik Tok Social Media) - Andini Srikandi; Usiono (JOURNAL SAINS STUDENT RESEARCH, 2025)
Tik Tok is a social media application that allows users to create short videos or posts. This application is almost the same as social media Instagram. This application is widely used in everyday life ranging from children to adults as entertainment and finding information. This research uses descriptive qualitative research methods. The technique used in this research is documentation. The data source taken from this research is the tik tok account @onepercent.class data collected in the form of screenshots. The research used in this study uses the theory of diction and language style. There are several sentences in the tik tok @onepercent.class account that contain diction words. The types of diction contained are denotative and connotative, with the language styles used are persuasive, hyperbole, and descriptive. The main purpose of writing this research is to provide examples to readers of how to write good diction, and to find out the variety of diction contained in tik tok social media on the @onepercent.class account and its influence on Indonesian language learning. Another purpose of writing this research is as an innovation in diction learning, especially in diction writing in making quotes on the tik tok @onepercent account.